Digital freedom in physical form : Developing a flexible model for representation of product series - Björklund, Andreas; Agermo, Erik (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
This master thesis from Industrial Design Engineering, Product Design, at Luleå University ofTechnology, has been formulated and assigned by Polardörren AB. Today’s manufacturing companiesoften display their products by using sample products in physical stores. Polardörren AB is a doormanufacturing company located in northern Sweden and have a wish to be experienced as a creativeand flexible company. Competitors to Polardörren AB have started using digital software to let theircustomers experiment with the composition of their products. This provides huge possibilities inrepresentation, however, digital is not always better. Digital representations mean a complete lackof feeling for material or quality. Ideally you would be able to combine the freedom of the digitalworld with the feeling of the physical world, and this is where our model fits in perfectly. We havedeveloped a prototype that, with the use of modularity, can represent many of Polardörren AB’sproducts in an effective and compressed way. By using the same type of material as the companyuse in their regular products, we present the user with a similar feeling as from the real products.Neodymium magnets lets a consumer, in an easy way, create and explore custom-made designsbased on their personal needs and wishes. By involving the end-user in the design process, webelieve that the number of purchases of the company’s products, and the general opinion towardsthe company, will increase. This could lead to increased revenue for both resellers and manufacturer.During the development process of this prototype, areas such as industrial design, semiotics, userexperience and usability has been explored. Methods used in this project ranges from brainstormingand brainwriting to computer modelling and CNC-milling. If this prototype would replace one ofthe existing product samples at the reseller today, the cost for representation would be estimated togo down to one third of the cost today. By using material that the company already have in theirproduction today, ...